ANALYSIS ON STUDENTS’ NUMERACY SKILLS IN SOLVING PROPORTION PROBLEMS IN THE CONTEXTS OF CANDI UMBUL TRADITIONAL MARKET - Fitria Sulistyowati; Irmawati Irmawati; Noka Setya Maharani; Muhammad Irfan (Ethnomathematics Journal, 2023)
The weaknesses in students' abilities in applying mathematical concepts and rules to non-routine problems caused them difficulties in solving them. This study was aimed at analyzing students' numeracy skills in solving proportion problems with the contexts of Candi Umbul Traditional Market. The study was qualitative descriptive research involving two seventh-grade students in Indonesia as research subjects. The two student subjects were selected from 10 students who completed the numeracy task, one with the most correct answer and one with the most incorrect answer. The ten students who completed the numeracy task were the ones with the highest test scores among 32 students in the topics of proportion and social arithmetics. The research instruments used in the study were students' work sheets (in the form of essay tests) and interviews. The data analysis technique used was descriptive analysis. Findings show that not every student with high math scores had high numeracy skills. This is evident from the fact that students faced problems when completing proportion items in the context of Candi Umbul Traditional Market; they encountered difficulties in solving the problems. The results of this study are expected to serve as a reference for further research on students' numeracy skills.